Meningkatkan Pemahaman dan Nilai Kristiani Siswa melalui Model PBL di Kelas IV SD Katolik - Antonius Eko Wahyudi; Ansel Joko Prayitno (Sekolah Tinggi Pastoral Kateketik (STPKat) Santo Fransiskus Assisi Semarang, 2025)
This study is motivated by the low level of understanding and internalization of Christian values among fourth grade students at Mardi Wiyata 2 Catholic Elementary School Malang in their daily lives, especially at school. This issue is reflected in the students’ lack of awareness of noble life values, such as belittling other living beings and being careless while playing, which could potentially endanger themselves and others. The purpose of this research is to improve students' understanding and internalization of Christian values through the implementation of the Problem Based Learning (PBL) model. The method used is Classroom Action Research (CAR), which consists of two learning cycles. Data collection techniques include written tests and observations. In the first cycle, which used the interview method, students’ learning outcomes were low, with an average cognitive understanding of only 31.57% (6 students completed the lesson successfully, while 13 did not). After applying the PBL model in the second cycle, there was a significant improvement, with average understanding reaching 83.95% (all students completed successfully), showing a 52.38% increase. The internalization of Christian values also improved—from 45.20% in the first cycle to 93.42% in the second cycle—an increase of 48.22%, as shown by student behaviors more aligned with Christian values. The results of this study demonstrate that the Problem Based Learning (PBL) model is effective in enhancing students’ understanding and internalization of Christian values.